PELATIHAN PENGOLAHAN LIMBAH KERTAS MENJADI PRODUK KREATIF DI BANK SAMPAH RUKUN SANTOSO - Much. Djunaidi (Universitas Sanata Dharma, 2018)
Waste management can be an economic value activity. Waste that is considered useless can be recycled into products that have economic values. Garbage Bank Rukun Santoso is a community empowerment activity in Klaten Regency that has attempted to use waste to be processed into creative products. At this time, the Rukun Santoso Garbage Bank has used plastic waste to be processed into creative products that have improved the economy of the local people, especially from the income of women. This type of paper waste is currently not utilized to be processed into creative products. This community service activity is intended to provide training in the creation of creative products made from paper waste, so that it can be used by the Rukun Santoso community to supplement family income.